Influence of Millet Husks on the Physical, Mechanical and Thermal Performance of a Lightweight Bio-Based Concrete - Saloufou, Soubérou Gbèdossou; Doko, Valéry Kouandété; Chabi, Edem; Olodo, E. T. Emmanuel; GIBIGAYE, Mohamed (My University, 2025)
In the context of transitioning toward more sustainable construction materials, this study explores the impact of incorporating millet husks as an alternative to sand on the physical, mechanical, and thermal performance of lightweight concrete. Through a mixture design approach, five formulations were selected and thoroughly characterized. The analysis of iso-response curves enabled an in-depth assessment of the cross-effects between formulation parameters and their interactions on the final properties of the material. The results show that integrating millet husks leads to a significant reduction in density, reaching up to 21%, while maintaining notable mechanical performance. A balanced formulation of sand and fibers achieved a maximum compressive strength of 12.11 MPa, demonstrating that, under specific conditions, plant fibers actively contribute to the structural integrity of the composite. In tensile strength, the positive influence of fibers is even more pronounced, with a maximum resistance of 8.62 MPa, highlighting their role in enhancing material cohesion. From a thermal perspective, millet husks reduce both thermal conductivity and effusivity, thereby limiting heat transfer and accumulation within the composite. Iso-response curve analysis reveals that these effects are directly linked to the proportions of the constituents and that achieving an optimal balance between sand, fibers, and cement is key to maximizing performance. These findings demonstrate that the adopted approach allows moving beyond conventional substitution methods by identifying optimal configurations for the design of lightweight bio-based concretes that are both strong and insulating, thereby confirming the potential of millet husks in developing lightweight concretes suitable for sustainable construction applications.
Keywords: Lightweight bio-based materials; plant fibers; mixture design; iso-response analysis; formulation optimization; mineral; aggregate substitution